Pelatihan Media Pembelajaran Kahoot Untuk Meningkatkan Efektivitas Pembelajaran di SMP YAPIS Merauke - Ferry Irawan; Dharma Gyta Sari Harahap; Muh. Rafi'y (Jurnal Transformasi Pendidikan Indonesia, 2024)
The service activities carried out are a form of socialization regarding the use of Kahoot learning media for teachers. The aim is to train teachers to be more skilled in the learning process and ensure that learning effectiveness can be achieved properly. Every learning activity requires a process and learning activities must provide an interesting learning experience for students. The socialization of Kahoot learning media is a strategic step in making the learning process in the classroom more interactive. The learning process in junior high school requires interactive and innovative learning media so that students are actively involved in every learning process so that learning outcomes can be achieved optimally.